PERSPEKTIF EKOSISTEM DALAM PEKERJAAN SOSIAL - Hasugian, Fordolin (Istek Widuri Jakarta, 2015)
Historically, social work as a discipline and profession has a variety of approaches or perspectives are continuously evolving and proceed according era. Ecosystem perspective is the latter, which seeks to understand human beings in a comprehensive and holistic, both the physical and social environment. This perspective has been successful in influencing policy makers, practitioners, social work, and the teachers and students, including in curriculum design. Model job that carried the generalist in all dimensions of practice (micro, mezzo and macro), both graduates of undergraduate, masters, and doctoral degrees are required to master many methods, although a little convenience in analyzing and solving any psychosocial problems.Hegemony ecosystem perspective lately criticized, because the method for this is still considered not a coherent, holistic and comprehensive, but it is still fragmented. Unique framework can not be said as a theory or model that can provide the basis of social work intervention, because it has not been tested empirically, and is not supported by empirical evidence, so it is still a question. Analogous to the world of medicine, specialization has been based on a method or technique of medicine. Can social work master's degree graduates to become specialists in the methodology of handling the problem of delinquency, both for the mischief of a child or an adult? Become our thinking together, in order to avoid accidents of history again.